Association Mapping for Yield Attributing Traits and Yellow Mosaic Disease Resistance in Mung Bean [Vigna radiata (L.) Wilczek] - Rohilla, Versha; Yadav, Rajesh Kumar; Poonia, Atman; Sheoran, Ravika; Kumari, Gita; Shanmugavadivel, P. S.; Pratap, Aditya (Frontiers in Plant Science, 2022)
Mungbean (Vigna radiata (L.) Wilczek) is an important short duration grain legume widely known for its nutritional, soil ameliorative and cropping system intensification properties. The present study aimed at evaluating genetic diversity among mungbean genotypes and detecting genomic regions associated with various yield attributing traits and yellow mosaic disease resistance by association mapping. A panel of 80 cultivars and advanced breeding lines was evaluated for ten yield related and yellow mosaic disease resistance traits during kharif (monsoon) and summer seasons of 2018-19 and 2019-20. 164 genome-wide simple sequence repeat (SSR) markers were initially screened, out of which 89 were found polymorphic which generated 317 polymorphic alleles with an average of 3.56 alleles per SSR locus. The number of alleles at each locus varied from 2 to 7. The population genetic structure analysis grouped different genotypes in three major clusters and three genetically distinct sub-populations (SP-1, SP-2 and SP-3) with one admixture sub-population (SP-4). Both cluster and population genetic structure analysis categorized the advanced mungbean genotypes in a single group/sub-population and the released varieties in other groups/sub-populations, suggesting that the studied genotypes may have common ancestral history at some level. The population genetic structure was also in agreement with the genetic diversity analysis. The estimate of the average degree of linkage disequilibrium (LD) present at the genome level in 80 mungbean genotypes unveiled significant LD blocks. Over the four seasons, ten marker-trait associations were observed significant for yellow mosaic disease and four seed yield related traits viz., days to flowering, days to maturity, plant height, and number of pods per plant by MLM method. These associations may be useful for marker-assisted mungbean yield improvement programme and YMD resistance.